HUBUNGAN PARENTAL-PEER ATTACHMENT DENGAN SELF-ESTEEM PADA PEMAIN INTERNET GAMING - Tandyasraya, Renisa; Dewi, Zahrasari Lukita (MANASA, 2024)
There are many internet-based activities, one of which is internet gaming, which, at a certain level of frequency, can lead individuals to internet addiction. This research, conducted with meticulous attention to detail, aims to determine the relationship between parental-peer attachment and self-esteem as two factors that are closely related to internet addiction behavior. The study was meticulously conducted on 38 young adult male and female internet gaming players using the Inventory of Parent and Peer Attachment-Revised (IPPA-R) and the Self-Esteem Scale (SES). Data were rigorously analyzed using one-tailed Spearman statistical analysis. The results show a positive relationship between Parental-Peer Attachment and Self-Esteem in internet gaming players. The alienation dimension in Mother, Father, and Peer Attachment has the most significant relationship. Self-competence and Self-liking dimensions have a negative relationship, so that these two dimensions will decrease or increase if one dimension experiences a decrease or increase. Further studies on the other psychological factors that underly internet gaming behavior potentially support the prevention of addiction.